2019
DOI: 10.26480/ecr.02.2019.06.12
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Control Methods of the Alien Invasive Weed Mikania Micrantha: A Review

Abstract: Invasion of alien weed species is one of the most serious global problems. Different bioclimatic conditions of Nepal favor the introduction of different invasive alien weeds. Mikania micrantha (L.) Kunth is one of the well-established invasive alien weeds in the tropical and subtropical parts of eastern and central Nepal. M. micrantha was first reported in 1963 in the eastern part of Nepal and then spreading towards the western part, which is now recorded in over 20 Terai districts of Nepal. Its spread is caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Research by Murphy et al (2013) indicated that M. macrantha negatively impacts on habitat of the endangered one-horned rhinoceros in Chitwan National Park, affecting 44% of their habitat by suppressing grass growth and tree regeneration. In the terrestrial ecosystem of Chitwan National Park, M. macrantha is identified as the most severe weed that extends to the northern part of the core and buffer zone area weed as IAP (Poudel et al 2019). Mikania macrantha is invasive and affects vegetation structure and carbon sequestration in ecosystems (Ulak et al 2016), creating an unfavorable environment for the growth of native species.…”
Section: Impact Of the Invasive Alien Plant Species On Terrestrial Ec...mentioning
confidence: 99%
“…Research by Murphy et al (2013) indicated that M. macrantha negatively impacts on habitat of the endangered one-horned rhinoceros in Chitwan National Park, affecting 44% of their habitat by suppressing grass growth and tree regeneration. In the terrestrial ecosystem of Chitwan National Park, M. macrantha is identified as the most severe weed that extends to the northern part of the core and buffer zone area weed as IAP (Poudel et al 2019). Mikania macrantha is invasive and affects vegetation structure and carbon sequestration in ecosystems (Ulak et al 2016), creating an unfavorable environment for the growth of native species.…”
Section: Impact Of the Invasive Alien Plant Species On Terrestrial Ec...mentioning
confidence: 99%
“…Pioneering description of certain IAPs like Mikania micrantha in N.E. India rated these species as aggressive invaders, covering the canopy of even the tallest trees (Tripathi et al 2011;Poudel et al 2019). This aggressive spread of M. micrantha (family Asteraceae) in N.E.…”
Section: Prospects Of Research On Plant Invasion Ecology In North East Indiamentioning
confidence: 99%
“…According to statistics, for every 1 km highway construction in our country, the area of bare slope is about 50-70,000 m 2 , and the area of slope formed by highway construction in our country is about 200-300 million m 2 every year. As a result, the area of high and steep bare rock slope is also increasing (Wood et al 2017), (Poudel et al, 2019). At present, one of the key technologies for artificial ecological restoration of such damaged slopes in China and abroad (such as hydraulic spraying, vegetation concrete slope protection greening, threedimensional vegetation net spraying grass planting, thick base material spraying vegetation slope protection, slope TBS vegetation slope protection greening, etc.)…”
Section: Introductionmentioning
confidence: 99%